Inhibition of Monosodium Urate Crystal-Induced Inflammation by Withaferin A - Rasool, Mahaboobkhan; Chandal, Sonal; Sabina, Evan Prince (Journal of Pharmacy & Pharmaceutical Sciences, 2009)
ABSTRACT Purpose. Gouty arthritis is a characteristically intense acute inflammatory reaction resulting from the formation of sodium urate crystals in the joint cavity. In the present study, the effect of withaferin A, a steroidal lactone was investigated on monosodium urate crystal-induced inflammation in mice; an experimental model for gouty arthritis and compared it with that of the non-steroidal anti-inflammatory drug, indomethacin. Methods. Paw volume and levels/activities of lysosomal enzymes, lipid peroxidation, anti-oxidant status and inflammatory mediator TNF-α were determined in control and monosodium urate crystal-induced mice. The levels of β-glucuronidase and lactate dehydrogenase were also measured in monosodium urate crystal-incubated polymorphonuclear leucocytes (PMNL). Results. Paw volume, the levels of lysosomal enzymes, lipid peroxidation, and inflammatory mediator tumour necrosis factor-α were found to be increased significantly and the activities of antioxidant status were in turn decreased in monosodium urate crystal-induced mice; however these changes were reverted back to near normal levels in withaferin A (30 mg/kg/b.wt, i.p.) treated monosodium urate crystal-induced mice. In addition, β-glucuronidase and lactate dehydrogenase level were reduced in withaferin A (100μg/ml) treated monosodium urate crystal-incubated polymorphonuclear leucocytes. Conclusion. The present findings clearly indicated that withaferin A exerted a strong anti-inflammatory effect against gouty arthritis.